Effects of human placenta‐derived mesenchymal stem cells with NK4 gene expression on glioblastoma multiforme cell lines. Issue 2 (8th October 2019) - Jabbarpour, Zahra; Kiani, Jafar; Keshtkar, Somayeh; Saidijam, Massoud; Ghahremani, Mohammad H.; Ahmadbeigi, Naser
Abstract: Poor prognosis and low survival are commonly seen in patients with glioblastoma multiforme (GBM). Due to the specific nature of solid tumors such as GBM, delivery of therapeutic agents to the tumor sites is difficult. So, one of the major challenges in the treatment of these tumors is a selection of appropriate method for drug delivery. Mesenchymal stem cells (MSCs) have a unique characteristic in migration toward the tumor tissue. In this regard, the present study examined the antitumor effects of manipulating human placenta‐derived mesenchymal stem cells (PDMSCs) with NK4 expression (PDMSC‐NK4) on GBM cells. After separation and characterization of PDMSCs, these cells were transduced with NK4 which was known as the antagonist of hepatocyte growth factor (HGF). The results indicated that engineered PDMSCs preferably migrate into GBM cells by transwell coculture system. In addition, the proliferation of the GBM cells significantly reduced after coculture with these cells. In fact, manipulated PDMSCs inhibited growth of tumor cells by induction of apoptosis. Our findings suggested that besides having antitumor effects, PDMSCs can also be applied as an ideal cellular vehicle to target the glioblastoma multiforme. Abstract : We indicated that NK4‐MSCs inhibited the glioblastoma cancer progression in vitro. The proliferation of glioblastoma multiforme (GBM) cell lines was inhibited by induction of apoptosis. This NK4‐MSC‐based therapy could, therefore, be an interesting drug‐delivery system for tumor homing and then cancer treatment. This approach can be applied as a powerful and safe strategy for targeting the microenvironment of tumor cells.